Trans Health in Argentina. A Review of Publications in Scientific Journals (2012-2021) - Farji Neer, Anahí (2023)
This work addresses different ways of approaching to transgender people`s health in Argentina by the scientific field after the enactment of Argentina´s Gender Identity Law (Law No. 26743). A literature review of scientific articles published between 2012 and 2021 from the electronic databases SciELO, PubMed and LILACS that addressed health issues related to the transgender population in Argentina was conducted. Two ways of producing knowledge on transgender health were identified. The first one used the concept of stigma as a starting point to explain different processes of social vulnerability that have an impact on the health of the transgender population. The second one focused on different responses to the violation of the rights of the transgender population in health institutions elaborated by the transgender population and within health institutions.